PENERAPAN MEDIA KARTU UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA DI SEKOLAH DASAR - Ratnasari, Desi; Halidjah, Siti; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis study aims to determine the skills of reading the students of class V students of State Elementary School 16 Pontianak City. The research method used in this research is descriptive method and the nature of research that is qualitative. The data source is VA class student which amounts to 27 people. The place of study took place at State Elementary School 16 Pontianak City, especially in VA class and the research time of odd semester 2017. Data collection techniques used are observation sheet and document scrutiny sheet with data collection tool that is the assessment sheet of card media planning and observation sheet of card media implementation , as well as test questions. From the data that has been obtained can be concluded that the ability of teachers to design learning (RPP) using the steps of the average media card score for the cycle I of 3.49, cycle II of 3.60, and in the third cycle of 3.86 included category well, the ability of teachers to implement the average on the first cycle of 3.02, in cycle II average score 3.63 and in cycle III average score 3.94 including good media category in advance and use time as well as possible . Improving students' reading comprehension skills, based on the results of the test in the first cycle average score of 55.57, on the second cycle average score of 76.74 and in cycle III the average score of 78.70. This means that the application of card media on reading comprehension material is good and can improve learning result Indonesian Grade V students of Dasra Negeri 16 Pontianak Kota School. Suggestions on using preparing media cardsÂ Keywords: Application, Card Media, Reading Comprehension Skills